EXPERIMENTING WITH LANGUAGE THROUGH CREATIVE WRITING TASKS - Christine Manara (Indonesian JELT, 2015)
This article reports a small-scale study that explores ways ofusing creative writing tasks to address learners’ motivationaland anxiety challenges in English writing. The study adopts anaction research design (Burns, 2010) with cycles of reflection,planning, implementation, evaluative reflection, and analysis.The study was conducted for one semester with 41 students oflow intermediate level of English proficiency participating inthe research. The data was gathered through the researcher’sclassroom observation, learners’ writing products, and lessonplan reflections and evaluations. The result of the study showsthat 1) learners are able to produce personal and meaningfulshort creative texts; 2) creative writing tasks encouragelearners to be a self-directed and autonomous English learner;3) creative writing tasks allow learners to experiment withtheir current vocabulary knowledge and produce linguisticcreativity; and 4) creative writing tasks expand their lexemeand senses knowledge.Keywords: teaching methodology, L2 writing, creativewriting task, action research